The relationship between adiposity, bone density and microarchitecture is maintained in young women irrespective of diabetes status. (4th August 2017) - Abdalrahaman, N.; McComb, C.; Foster, J.E.; Lindsay, R.S.; Drummond, R.; McKay, G.A.; Perry, C.G.; Ahmed, S.F.
Summary: Background: The relationship between bone health and adiposity and how it may be affected in people with chronic metabolic conditions is complex. Methods: Seventeen women with type 1 diabetes mellitus (T1DM) and nine age‐matched healthy women with a median age of 22.6 years (range, 17.4, 23.8) were studied by 3T MRI and MR spectroscopy to assess abdominal adiposity, tibial bone microarchitecture and vertebral bone marrow adiposity (BMA). Additional measures included DXA‐based assessments of total body (TB), femoral neck (FN) and lumbar spine (LS) bone mineral density (BMD) and fat mass (FM). Results: Although women with T1DM had similar BMI and BMA to the controls, they had higher visceral and subcutaneous adiposity on MRI ( P <.05) and total body FM by DXA ( P =.03). Overall, in the whole cohort, a clear inverse association was evident between BMA and BMD at all sites ( P <.05). These associations remained significant after adjusting for age, BMI, FM and abdominal adiposity. In addition, visceral adiposity, but not subcutaneous adiposity, showed a positive association with BMA ( r, .4, P =.03), and a negative association with total body BMD ( r, .5, P =.02). Apparent trabecular separation as assessed by MRI showed an inverse association to total body BMD by DXA ( r, −.4, P =.04). Conclusion: Irrespective of the presence of an underlying metabolic condition, young women display a negative relationship between MRI‐measured BMA and DXA‐based assessment of BMD. Furthermore, an association between BMA and visceral adiposity supports the notion of a common origin of these two fat depots.